Flu in children of the Astrakhan region - R. S. Arakelyan; A. E. Maslyaninova; D. N. Kasatkin; N. A. Abbasova; Kh. Kh. Saadueva; A. D. Kunkasheva; K. K. Nurusheva (Лечащий Врач, 2024)
Objective. The purpose of the study was to perform a retrospective analysis of the age-related morbidity of the children's population of the Astrakhan region for 2018-2022 in order to increase the effectiveness of preventive measures.Materials and methods. To study the age-related morbidity, an analysis of medical documentation (case history f. № 003/y) was carried out in 3436 children who sought medical help from the State Medical Institution of State Budgetary Healthcare Institution of the Astrakhan region Children's City Polyclinic No. 4 and the State Budgetary Healthcare Institution of the Astrakhan region Regional Infectious Clinical Hospital named after A. M. Nichogi. Depending on the age, the children were divided into groups: from 8 months to 1 year – group I (n = 288), from 1 to 7 years – group II (n = 1927), from 7 to 17 years – group III (n = 1221).The research work was carried out on the bases of the Federal Budgetary Healthcare Institution Center of Hygiene and Epidemiology in the Astrakhan Region and the Federal State Budgetary Educational Institution of Higher Education Astrakhan State Medical University of the Ministry of Health of the Russian Federation Federation.Results. During the analyzed period, more than 60% of all cases of influenza related to children (67.1%). These cases were registered in three age groups: from 8 months to 1 year, from 1 year to 7 years and from 7 to 17 years. The reported cases of influenza in children relate to the period from 2018 to 2022. The incidence of children of the first age group was 8.4% (n = 288), the second group – 56.1% (n = 1927), and the third group – 35.5% (n = 1221). The highest incidence was recorded in 2019 and amounted to 34.6% (n = 1098). This year, the incidence was as follows: the first group – 7.7% (85 cases), the second group – 58.7% (n = 644) and the third group – 33.6% (n = 369). The lowest incidence in children was registered in 2022 and amounted to 7.8% (n = 273), where the first group was 16.8% (n = 46), the second group was 39.9% (n = 109), and the third group was 43.3% (n = 118). The majority of cases of influenza were registered in children living in urban areas – 93.6% (n = 3216). At the same time, the first group was 6.6% (n = 211), the second group was 57.3% (n = 1846), and the third group was 36.1% (n = 1159). In rural areas, the third age group with 63.9% (n = 141) cases is the most susceptible to the disease, the second group is 23.5% (n = 51), and the first group is 12.6% (n = 28).Conclusion. Based on the data, it can be concluded that H3N2(A) influenza was the most common strain of influenza among children in the period from 2018 to 2022. The main symptoms of influenza in children included fever, weakness, fatigue, headache, myalgia or arthralgia. Some children also complained of pain when swallowing, runny nose, cough, vomiting and diarrhea. These data will help to better understand the nature of influenza in children and take appropriate measures to prevent and treat it. Taking care of children's health should be a priority for everyone – parents, medical professionals and government agencies. Only through joint efforts will we be able to reduce the incidence of influenza among children and create a healthier future for our society.